Conserved P-TEFb-interacting domain of BRD4 inhibits HIV transcription. - Bisgrove, D.A.; Mahmoudi, T.; Henklein, P.; Verdin, E. (Proceedings of the National Academy of Sciences of the United States of America, 2007)
We have identified a conserved region in the C-terminal domain of bromodomain-containing protein 4 (BRD4) that mediates its specific interaction with positive transcription elongation factor b (P-TEFb). This domain is highly conserved in testis-specific bromodomain protein (BRDT) and Drosophila fs(1)h. Both BRDT and fs(1)h specifically interact with P-TEFb in mammalian cells, and this interaction depends on their C-terminal domains. Overexpression of the BRD4 P-TEFb-interacting domain disrupts the interaction between the HIV transactivator Tat and P-TEFb and suppresses the ability of Tat to transactivate the HIV promoter. Incubation of cells with a synthetic peptide containing the C-terminal domain of BRD4 interferes with transactivation of the HIV promoter by the Tat protein.